2017
DOI: 10.1016/j.cortex.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The attribution of animacy and agency in frontotemporal dementia versus Alzheimer's disease

Abstract: Impaired attribution of animacy (state of living or being sentient) and of agency (capability of intrinsically-driven action) may underlie social behavior disturbances in behavioral variant frontotemporal dementia (bvFTD). We presented the Heider and Simmel film of moving geometric shapes to 11 bvFTD patients, 11 Alzheimer’s disease (AD) patients, and 12 healthy controls (HCs) and rated their recorded verbal responses for animacy attribution and agency attribution. All participants had skin conductance (SC) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Two articles explored attribution bias; one observed similar performance in patients with both types of dementia (Cova et al, 2012 ), while the other reported a specific animacy attribution impairment in patients with bvFTD (Fong et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%
“…Two articles explored attribution bias; one observed similar performance in patients with both types of dementia (Cova et al, 2012 ), while the other reported a specific animacy attribution impairment in patients with bvFTD (Fong et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%
“…The affective component of mentalization is impaired early in bvFTD (Adenzato et al, 2010;Bora et al, 2015;Dodich et al, 2016;Henry et al, 2014;Orso et al, 2020;Pardini et al, 2013;Poletti et al, 2012Poletti et al, , 2013Torralva et al, 2015), and individuals with bvFTD exhibit decreased performance on moral dilemmas, where they do not foresee negative emotional reactions when contemplating directly harming others (Greene and Haidt, 2002;Greene et al, 2001). Furthermore, when viewing moving geometric shapes (Fong et al, 2017), individuals with bvFTD who have right IFG atrophy show significantly decreased anthropomorphization compared with controls. Additional evidence for impaired "humanness" perception is that individuals with frontotemporal dementia who are artists, specifically caricaturists, may draw others in a progressively distorted, nonhuman, or "alien" fashion as their dementia progresses (Mendez and Perryman, 2003).…”
Section: Evidence From Brain Disordersmentioning
confidence: 99%
“…An impairment in theory of mind abilities has been extensively described in bvFTD (222, 223). Deficits have been observed using different paradigms based on false-belief (224226), detection of sarcasm (210, 227) or insincere communication (228), agency attribution (229), as well as emotional inference or attribution (209, 230, 231), emotional movement-based inference (232) and social faux pas detection and understanding (207, 209, 212, 213). While similar deficits may be observed in AD as well [e.g., (225, 229) for a review, see (233)], they seem to be variable and to depend on the severity of the disease.…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 99%
“…Deficits have been observed using different paradigms based on false-belief (224226), detection of sarcasm (210, 227) or insincere communication (228), agency attribution (229), as well as emotional inference or attribution (209, 230, 231), emotional movement-based inference (232) and social faux pas detection and understanding (207, 209, 212, 213). While similar deficits may be observed in AD as well [e.g., (225, 229) for a review, see (233)], they seem to be variable and to depend on the severity of the disease. In contrast to AD, theory of mind deficits in bvFTD were only sparsely or not associated with other cognitive dysfunctions(209, 225, 232) and only little associations with other cognitive dimensions in bvFTD have been found when cluster-based or regression analyses specifically investing these relationships were employed (219, 220).…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 99%